ANALISIS BEBAN KERJA STAFF OUTBOUND GUDANG PADA PT. GUDI GOODANG.COM DENGAN METODE SUBJECTIVE WORKLOAD ASSESSMENT TECHNIQUE (SWAT) - Abiel Mahardhika Anggara; Darfial Guslan; Dani Leonidas Sumarna (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Every company strives to increase business, improve performance, and maintain profits. Therefore, to measure the success of the company, operational functions and employee productivity must be considered. Paying attention to each employee's workload is one component that increases employee productivity. PT. GUDI GOODANG.COM Is a company engaged in the logistics sector that focuses on goods storage services or warehouse service providers. Employees have an average overtime hour exceeding the limit stipulated in Article 26 Paragraph 1 PP. 35/2021. This is due to the large number of orders that must be completed and unfinished work during normal working hours. As a result, employees who work outside must work overtime to complete the scope of outside operational activities, where high overtime hours can trigger an increase in workload, where workload greatly influences the quality of employee performance. The subjective measurement method is the easiest and most accurate for estimating mental workload. The Subjective Workload Assessment Technique (SWAT) approach reveals three variations of the mental workload: time load, effort load, and psychological stress. From the results of the prototyping process it shows that the workload that gives the highest contribution is the time workload which is 71.76%, the Effort workload is 21.99% and the Stress workload is 6.25%. Company PT. GUDI GOODANG. It is necessary to always assess or calculate the workload of employees in order to know the condition of the employee's workload on an ongoing basis so that they can carry out optimal Human Resource management with an average workload that employees have.